Diversified image of a child with learning difficulties and parental help - Wiatrowska, Leokadia (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2013)
Learning is for every student a specific kind of difficulty, which generates successes and failures and emotional constituents bound with it during this form of a child’s activity. Particularly severe consequences of learning process are experienced by students with developmental deficits which prevent normal functioning as a student through creating problems in the process of acquiring knowledge. Discrepancies between school’s requirements and child’s abilities occurring in such situation create an unpleasant mental situation of a student both in school and at home. In such a situation parents and their support, which comes in many forms and extents, are of important relevance.
Keywords: learning; child; difficulties in learning; parents; parental help; supporting